2013
DOI: 10.1186/1471-2121-14-22
|View full text |Cite
|
Sign up to set email alerts
|

Constant or fluctuating hyperglycemias increases cytomembrane stiffness of human umbilical vein endothelial cells in culture: roles of cytoskeletal rearrangement and nitric oxide synthesis

Abstract: BackgroundPrevious studies have implicated continuous or intermittent hyperglycemia in altered endothelium-derived nitric oxide (NO) synthesis. NO can regulate both the F-actin cytoskeleton and endothelial cell membrane stiffness. Atomic force microscopy (AFM) is a powerful tool that can be used to study plasma membrane deformability at the single cell level. As membrane stiffness is partially dependent on filamentous F-actin, the interdependence of these parameters can be studied through the combined approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…These processes exacerbate the oxidative stress [ 33 35 ] which damages cells and induces apoptosis [ 36 , 37 ]. Apoptosis may be promoted also by DNA damage [ 11 , 38 ] and irreversible changes in cytoskeletal organization at high glucose concentration [ 39 , 40 ]. IL-6 secreted during the acute phase of inflammation has varied effects on cells in diabetes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These processes exacerbate the oxidative stress [ 33 35 ] which damages cells and induces apoptosis [ 36 , 37 ]. Apoptosis may be promoted also by DNA damage [ 11 , 38 ] and irreversible changes in cytoskeletal organization at high glucose concentration [ 39 , 40 ]. IL-6 secreted during the acute phase of inflammation has varied effects on cells in diabetes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia, particularly the fluctuation of glucose levels, causes a significant oxidative stress, decreasing the expression of endothelial nitric oxide synthase and impairing NO metabolism [ 34 ]. Fluctuating hyperglycemia induces an increased production of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that variability in glycaemic control is more deleterious to endothelial cells than persistent hyperglycaemia. For example, some previous studies reported that fluctuating or intermittent high glucose increased expression of adhesion molecules ICAM-1, VCAM-1, and E-selectin [ 42 ], augmented apoptosis [ 43 ], and downregulated NO production [ 44 ]. No studies have investigated hyperglycaemia per se on human SV-EC angiogenesis but the failure of intensive glycaemic control to normalise macrovascular complications in T2DM in the medium term (ACCORD, ADVANCE, and VADT clinical trials [ 5 , 6 ]) suggests involvement of other factors.…”
Section: Discussionmentioning
confidence: 99%